Analisis Pengaruh Rx Level Terhadap Kecepatan Download Data Pada Teknologi GPRS di PT XL Axiata Tbk. Purwokerto - Aldina Peto Bravi; Azis Wisnu Widhi Nugraha; Widhiatmoko Hery Purnomo (Dinamika Rekayasa, 2011)
Data transfer speed on GPRS’s technology isaffected by the present of some obstacles between sender’s side and recipient’s side. Those obstacles cause propagation loss that affect the reduction of power level value (rx level). The reduction will affect the data speed. The lower rx level’s value means the lower dataspeed. This researchwas done by doing drive test on BTS North Purwokerto and BTS Tambaksogra to measure the amount of power measured (Pr) andthe download data speed on GPRS’s network. The measuredpower level (Pr) was normalized to get rx level value. Regression analysis was done to get the relation between the download speed and the rx level value. Theanalysis has resulted in a model: download speed = 4.1 (rx level) 0.459 , with R^2 = 0.380. Correlation analysis shows high correlationbetween rx level and download speed (r = 0.608).